Effect of motoring voltage on compression ratio of a free-piston linear generator engine - Zainal A., E.Z. (Universiti Malaysia Pahang, 2015)
The need for alternative power sources is crucial because of the increase in global energy demand and stringent emission regulations. The free-piston linear generator engine is one of the main alternatives thanks to its high efficiency, wide operating range and low emissions. However, low compression pressure which produces low power generation is an obstacle to its development. In order to increase compression pressure, further development of the motoring process is required. The study investigated the effect of motoring voltage in compression pressure and compression ratio. Motoring voltages varied from 36 V to 84 V. Higher motoring voltage increased piston speed up to 2 m/s which reduced the air leakage and thus produced a sharper p-V profile and higher compression pressure. An inverse relationship between the compression ratio and compression pressure during motoring was also observed. Â© Universiti Malaysia Pahang, Malaysia.